USING STORYTELLING TO MOTIVATE PROGRAMMING. - Kelleher, Caitlin; Pausch, Randy (Communications of the ACM, 2007)
The article discusses the use of storytelling to motivate the study of computer programming. The authors examine the inclusion of the Storytelling Alice programming environment, which allows users to create computer-animated movies, as a motivational tool for middle school girls. Programs like Storytelling Alice are especially important in the 2000s, as student interest in computer science is falling in the United States, largely because students believe that the subject is boring from as early as grade school.